PENGUKURAN LITERASI DIGITAL SISWA SMA PRAMITA DI TANGERANG - Suhartono Chandra (PROSIDING SERINA, 2021)
Technology and media can empower people. One can get much personal benefits, social and culture from making wise decision toward information, using digital tools to self-expression and communicate, and participate in online community with people over the world in sharing interest and attention. But one should have protection to build self-defence toward the negative impact, annoying, disturbance or un-approriate. That is why high school students need new competency what we called digital literacy. Digital literacy become very important and should be a part of curricula at school. Nevertheless, many schools have not ready yet embracing digital literacy as basic literacy like reading, writing, and counting. Digital literasi consist of five dimensions; information literacy, computer literacy, media literacy, communication literacy, technology literacy and three perspektives; coqnitive, technical, and ethical. This research aims to measure digital literacy index of high school student of SMA Pramita in Tangerang using survey method. Data were collected by e-form and analysed with statistic analysis multivariat/structural equation modelling (SEM) using software R version 4.0.5. 171 students grade X, XI, and XII were participated. The result shows that level of students’ digital literacy between fair to good with mean sore was 3,78 from 5,00 scale. AVE score is 0,59 which is greater than 0.50 and CR is 0.878 also greater than 0.700.